Fertility preservation and PGT-M in women with familial adenomatous polyposis-associated desmoid tumours. Issue 4 (October 2021) - Fouks, Yuval; Sheiman, Vadim; Goaz, Sher; Malcov, Mira; Hasson, Yossi; Azem, Foad
Abstract: Research question: Is ovarian stimulation and pregnancy in women with familial adenomatous polyposis (FAP)-associated desmoid tumours safe? Design: The study included women with FAP-associated desmoid tumours who underwent fertility treatments at the authors' tertiary medical centre between the years 2011 and 2021. Data were collected from the fertility unit's charts and from the oncological registries. The main outcome measures were the number of vitrified oocytes and embryos, and the number of live births in preimplantation genetic testing for monogenic/single gene defects (PGT-M) cycles. Results: Overall, 17 women were identified suitable for this study. A total of 117 mature oocytes were vitrified for fertility preservation and 106 embryos were submitted to PGT-M. One patient returned to claim her cryopreserved oocytes, and five patients who underwent PGT-M embryo transfer reported three live births. A statistically significant decrease in selected fertility cycle parameters was observed in one woman who co-administered sorafenib (a multikinase inhibitor) during her first cycles of treatment, as the mean number of oocytes before and after was 2.7 (±1.3) versus 13.2 (±3.3) ( P = 0.02), the mean number of metaphase II oocytes was 2.2 (±2.1) versus 7.7 (±2.6) ( P = 0.007), and the mean number of two-pronuclei oocytes was 0.5 (±1.1) versus 3.5 (±1.7) ( P = 0.09). Three patients had a median desmoid tumour growth on magnetic resonance imaging of 6.2 (2.9–7.2) cm when compared with prior ovarian stimulation imaging. Conclusions: Ovarian stimulation for women with desmoid tumours was characterized in some patients with an acceleration in tumour growth, regardless of the use of aromatase inhibitors. The use of sorafenib should be carefully considered during the course of fertility treatment.